Pyogenic Granuloma: Surgical Treatment with Er:YAG Laser - Fekrazad, Reza; Nokhbatolfoghahaei, Hanieh; Khoei, Farzaneh; AM Kalhori, Katayoon (Journal of Lasers in Medical Sciences, 2014)
Introduction: Pyogenic granuloma (PG) is a common tumor-like growth of the oral cavity, considered to be of non-neoplastic nature, often caused by constant low-grade trauma as well as poor oral hygiene and maybe due to hormonal disturbances. Surgical excision, and removal of underlying cause in some cases, is the preferred method of treatment as it is only a benign lesion. In order to remove this lesion, scalpel, cryosurgery and laser are used. Currently different lasers, with adequate parameters, are used for the surgery of PG, which include CO2 (Carbon Dioxide Laser), Nd:YAG (Neodymium-Doped Yttrium Aluminium Garnet), Diode and Er Family amongst others. In this present case, due to the proximity of the lesion with dental hard tissue, Er:YAG (Erbium-Doped Yttrium Aluminum Garnet) laser appears to be the more appropriate laser. The application of Laser is also a newly recommended technique. The aim of this study is to assess the stages of treatment, recovery and recurrence of PG when the Er:YAG laser is used. Furthermore this study aims to also evaluate the friendliness of this method with regards to the surgeon (therapist). Case report: A 24-year-old female was referred to the Laser Research Center of Dentistry of Tehran University of Medical Sciences with a complaint of gingival overgrowth and bleeding. This lesion was in the buccal and palatal side of the 5 and 6 maxillary teeth. Treatment plan included an excisional biopsy of the lesion using Er:YAG laser (3W, 300mJ, 10Hz, Short pulse, with contact headpiece). The bones were then cleaned of soft tissue before being smoothed using a curette. The excised specimen was preserved and sent for histopathological examination. Results: The patient reported no pain after surgery and did not use any systemic antibiotics. The patient was satisfied after the surgery. Chlorhexidine mouthwash was given to the patient. Pathology results confirmed Pyogenic granuloma. After 2 weeks, complete healing was observed. The 9-month follow-up was also carried out in order to check the process of healing as well as the recurrence. Conclusion: Excisional surgery is the preferred treatment method for PG. The application of laser can be considered as an effective and safe technique for excision of this lesion with minimal invasion and many clinical advantages such as less intra-operative bleeding, hemostasis and reduced pain and times of healing.